2019
DOI: 10.3390/min9100606
|View full text |Cite
|
Sign up to set email alerts
|

Ore Geology, Fluid Inclusion Microthermometry and H-O-S Isotopes of the Liyuan Gold Deposit, Central Taihang Mountains, North China Craton

Abstract: The Liyuan gold deposit, located in the central Taihang Mountains, North China Craton, forms an important part of the Taihang polymetallogenic belt. The origin of ore-forming fluids and the genesis of this deposit remains controversial. In this paper, fluid inclusions (FIs) microthermometry and H-O-S isotopes analysis are conducted to constrain the origin of ore-forming fluids and genesis. The main findings are as follows: (1) Three hydrothermal metallogenic stages are identified: Quartz–pyrite, quartz–polymet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 84 publications
(150 reference statements)
0
8
0
Order By: Relevance
“…However, these ratios will have a large range when hydrothermal activity is affected by metasomatism or other hydrothermal activities [82,83]. In this study, the Y/Ho values of pyrite (24.6-34.4) were similar to those of the mantle (25)(26)(27)(28)(29)(30), indicating the contribution of mantle materials. The Zr/Hf and Nb/Ta ratios of pyrite in the Miaoan Au deposit vary widely (19.4-243 and 4.38-70.0).…”
Section: The Properties Of the Ore-forming Fluidsmentioning
confidence: 47%
See 1 more Smart Citation
“…However, these ratios will have a large range when hydrothermal activity is affected by metasomatism or other hydrothermal activities [82,83]. In this study, the Y/Ho values of pyrite (24.6-34.4) were similar to those of the mantle (25)(26)(27)(28)(29)(30), indicating the contribution of mantle materials. The Zr/Hf and Nb/Ta ratios of pyrite in the Miaoan Au deposit vary widely (19.4-243 and 4.38-70.0).…”
Section: The Properties Of the Ore-forming Fluidsmentioning
confidence: 47%
“…Studies in recent years have shown that the northern Taihang Mountain (TM), west of the NCC destruction zone, developed a large number of gold deposits, such as the Shihu, Yixingzhai, Liyuan, and Gengzhuang gold deposits (Figure 1a). However, these deposits have received relatively less attention [13,[24][25][26][27]. This is not conducive to understanding the genesis of Mesozoic gold deposits in the entire NCC destruction zone.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of type 3a FI in the late‐stage indicates that at the culmination of the mineralisation, the ore fluid composition changes into the H 2 O‐NaCl dominant fluid. In addition, FI trapped during the late stage of mineralisation has low temperature and salinity because of the mixing of ore‐forming fluid with meteoric water, which indicated that the ore‐bearing fluids underwent cooling and dilution (Hedenquist & Henley, 1985; Lawrence et al, 2013; Pollard, 2006; Shepherd et al, 1985; Tan, Xia, Xie, & Yan, 2015; Ulrich, Guenther, & Heinrich, 2001; Wilkinson, 2001; Zhu et al, 2019). On the other hand, secondary inclusions were formed along the fracture that developed at the later stage of deformation at the end stage of crystallization of minerals.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it shows that fluid immiscibility might be the major process from which the original aqueous gaseous (H 2 O‐NaCl‐CO 2 ± N 2 ) fluid separated into gaseous (CO 2 ± N 2 ) and saline aqueous fluid (H 2 O‐NaCl). (Pichavant, Ramboz, & Weisbrod, 1982; Zhu et al, 2019). Some inclusions homogenized at above 400°C have a slight variation in salinity, indicating the separation of moderately saline fluid from the granitic melt (Jackson, Willis‐Richards, Manning, & Sams, 1989; Shepherd et al, 1985) (Figure 11b).…”
Section: Discussionmentioning
confidence: 99%
“…The scanning range for the spectra lay between 100 and 4000 cm −1 , with an accumulation time of 10 s for each scan and a spectral resolution of 1-2 cm −1 . The detailed procedures followed those reported in previous studies [53][54][55][56].…”
Section: Fluid Inclusion Microthermometrymentioning
confidence: 99%